2012
DOI: 10.48550/arxiv.1208.1256
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Casimir expulsion of periodic configurations

Abstract: There is the possibility in principle that the noncompensated Casimir force exists in open nanosized metal cavities arranged in the form of periodic structures. It is found that when trapezoid cavities are strictly periodic all the Casimir expulsion forces are completely compensated. However, when the distance of the gap is formed between the cavities, in the periodic configuration a noncompensated expulsion force proportional to the number of cavities appears. There are such effective parameters of the period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…3a) is valid for periodically situated figures. A certain phenomenon [6] has been found; when plates are placed at absolutely equal distances d = a from one another, there is no expulsion in the entire configuration (see Fig. 3b).…”
Section: What Is Casimir Expulsion?mentioning
confidence: 98%
See 2 more Smart Citations
“…3a) is valid for periodically situated figures. A certain phenomenon [6] has been found; when plates are placed at absolutely equal distances d = a from one another, there is no expulsion in the entire configuration (see Fig. 3b).…”
Section: What Is Casimir Expulsion?mentioning
confidence: 98%
“…Combined finding of maxima using all possible parameters according to formula (8) in Ref. [6] allows to find for the angle ϕ ≈ 1 optimal relations d/a → 1.65 and R/a → 1.8 for given geometry of the configuration of planes.…”
Section: Estimates Of Expulsion Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…In formula (2), = h/2π -reduced Planck constant, and c-light speed; the functional expressions for the figure limit angles Θ right 1 , Θ right 2 for the right wing in the con-figuration taking into account relative shifts ∆x have the following form [16] Θ right…”
Section: Theorymentioning
confidence: 99%
“…In our case, the drag effect can occur in nonparallel and well-conducting wings due to the resultant uncompensated action of virtual photons on electrons. Earlier it has been shown that in principle, in addition to the excitation of an EMF, the system with nonparallel wings can experience Casimir expulsion force [15] and have some other interesting effects [16,17]. The uncompensated action of forces on nonparallel configurations is due to the nonuniform action of Casimir forces on the opposite ends of the configuration asymmetrical along one of the coordinates.…”
Section: Introductionmentioning
confidence: 99%